Spatial distribution and seasonal profile of parasitic contamination in sewage water samples from the city of Santana do Ipanema, Northeast region of Brazil - P. D. Lima; Vitória Jordana Bezerra Alencar; João Paulo Vieira Machado; Aécio Prado Lima Júnior; Maria Wilma da Silva Lima; Laryssa Oliveira Silva; Sheilla Conceição Gomes; Martha Rejane Souza Bispo; Ádrian Cabral Silva; Letícia Pereira Bezerra; Tatyane Martins Cirilo; Wandklebson Silva da Paz; et al. (IWA Publishing, 2023)
Wastewater released into the environment without proper treatment contributes to the high prevalence of parasitic infections. We aimed to investigate the occurrence of parasites in sewage waters in both rainy and dry seasons in the city of Santana do Ipanema, Brazil. This is a descriptive cross-sectional study carried out between the months of June, July (rainy season) and October (dry season) of 2021. A total of 50 streets were selected by a sample calculation in the Epi Info™ program. From each street, two wastewater samples were collected in both climatic periods. In the laboratory, the water samples were submitted to the Bailenger method with some adaptations and analyzed under an optic microscope. In the rainy season, we detected Strongyloides stercoralis (87.6%; 134), Strongylus spp. (4.6%; 7), hookworms (2.0%; 3) and Iodamoeba butschlii (62.5%; 5), and in the dry season, it was detected S. stercoralis (55.0%; 71), Metastrongylids (19.4%; 25), hookworms (12.4%; 16) and I. butschlii (76.5%; 13). The spatial analysis has shown that most hotspots were associated with S. stercoralis, mainly during periods of intense rainfall and close to river areas. Thus, the city population is subject to infections, especially by helminths regardless of seasonality. HIGHLIGHTS S. stercoralis was the most frequent helminth in both weather periods.; High concentrations of hookworms, Metastrongylids and I. butschlii were observed during the dry season.; A precise technique for collecting water directly from open sewers has been described.; The Bailenger method with the adaptations reported here became a cheap and efficient technique for parasite detection in sewage water.;